Guillain Barre Syndrome (GBS) in Cape Town, South Africa: a descriptive outcomes cohort study - Chetty, Sarvani (Department of Medicine, 2020)
INTRODUCTION Guillain-Barré syndrome (GBS) or acute inflammatory demyelinating polyradiculoneuropathy (AIDP) is an important cause of acute severe and life-threatening weakness. It occurs worldwide and may affect all age groups, but varies widely in clinical presentation, subtype, electrophysiology, course and outcome. There is sparse literature on GBS in low and middle income countries (LMIC), and the effect, if any, of HIV on GBS. This observational cohort study aims to describe the clinical presentation and outcome of acute GBS in Cape Town, South Africa, in participants recruited into the International Guillain-Barré Syndrome Outcome Study (IGOS). A secondary aim, given the high HIV prevalence in South Africa, is to describe and compare GBS participants with and without HIV infection. METHODS Between 1 June 2014 and 31 January 2017, we recruited participants 18 years or older presenting to Groote Schuur Hospital in Cape Town with acute GBS (< 2 weeks onset of symptoms) who were available for 1 year follow up. We recorded demographic, clinical, laboratory, electrophysiological and treatment data at entry. At follow-up at weeks 4, 26 and 52, GBS-related complications and GBS disability scale scores (GDSs) were evaluated. A good outcome was defined as the ability to walk unaided (GDSs 2) by 6 months. The clinical presentation and outcomes of HIV-uninfected and -infected participants were compared. RESULTS: Of 31 recruited participants, 1 participant was re-diagnosed as acute onset-CIDP and excluded from the study and 1 participant demised of an unrelated cause within the first week. 19 participants were male and the median age was 40 years. Reported antecedent infections (73%), co-morbid HIV infection (30%) and tuberculosis (15%) were frequently seen. Acute inflammatory demyelinating polyradiculoneuropathy (AIDP; 67%) and acute motor axonal neuropathy (AMAN; 17%) were the most common phenotypes. Overall, GBS-related complications occurred in 46% of participants. The major complication was pneumonia which occurred in 23% of the total group, and all required intubation/ventilation. Other septic complications (drip site or systemic) were less common, 6% of the entire group. At entry, 83% had GDSs >4 indicating severe disability. The ability to walk unaided was regained by 37% at 4 weeks, 75% at 6 months and 79% at 1 year. Three participants remained severely affected at 1 year (GDSs of >3). There were no differences in antecedent infections, treatments given, or motor outcomes between HIV-infected and -uninfected GBS participants apart from a trend towards higher CSF protein in the HIV-infected group (p-value 0.05). AIDP was the most common GBS variant in both groups. AMAN was only seen in the HIV-uninfected group, whereas Miller Fisher 5 syndrome (MFS) was more common in the HIV-infected group. However, the numbers were too small to reach statistical significance. CONCLUSION Infections with HIV and tuberculosis frequently co-occurred with acute GBS, whether this reflects true disease association or merely high background disease prevalence cannot be confirmed by this study. AIDP is the most common phenotype unlike other LMIC regions such as Asia where AMAN predominates. In this cohort, 76% of participants showed good outcomes being able to walk unaided or having no/minor symptoms by 6 months. However, of the remainder only 1 showed significant recovery at 1 year. HIV participants had similar clinical presentations, complications and outcomes compared to the HIV-uninfected group. Mortality was low.